Language and nationalism in South Asia - Hossain, Ishtiaq (2015)
It is argued in this paper that although the South Asian sub-continent was split into two independent states of Pakistan and India in 1947 on the basis of religion, in the post-independence years, in both states the question of national language emerged as a major issue in their national politics, and threatened to reshape their religion-based nationalism. It would further argue that if not handled deftly by a national government, the controversies surrounding the national language policy may lead to the emergence of sub-nationalism, threatening the very unity of the state. We would use the example of Pakistan to make this point.